Functional, esthetic and psychological rehabilitation of a hemimaxillectomy patient with closed hollow bulb obturator - Raj K, Sounder; Gaur, Satyam; Srivastava, Rachana (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
The intraoral defects can either be congenital or acquired. The mostcommon defects lead to an opening in maxillary antrum and nasopharynx. Thesedefects usually affect variety of functions, including swallowing, drooling of oralsecretions, speech and mastication. Esthetic, functional and psychologicalrehabilitation of maxillo-mandibular complex is the ultimate goal of prosthodontictreatment. The treatment of choice for such defects is the fabrication of lightweighthollow obturator prosthesis. This case report presents rehabilitation of a 58-year-oldfemale with closed hollow bulb obturator who underwent hemi-maxillectomy withremoval of floor of orbit for squamous cell carcinoma.